2020
DOI: 10.32394/rpzh.2020.0142
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of exposure to nickel intake with selected cereal grains and cereal-based products

Abstract: Background. Cereal grains and their products are among the basic components of the diet all over the world. Their consumption varies depending on the dietary habits in each country. Apart from ingredients valuable from a health point of view, these products can also be a source of contaminants. The European Food Safety Authority (EFSA) included these foodstuffs in the group of main contributors to the dietary exposure to nickel by different groups of the population. Objective. The aim of the studies was to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In this contest, CS/Na‐Alg/PAAc was prepared via gamma irradiation as a vehicle for Ni nanoparticles. Ni is carefully nominated as it is benign at low concentrations 45 . Moreover, radiation‐induced copolymerization is applied as a quick, easy, and affordable way to make hydrogels when compared to chemical methods 46–48 .…”
Section: Introductionmentioning
confidence: 99%
“…In this contest, CS/Na‐Alg/PAAc was prepared via gamma irradiation as a vehicle for Ni nanoparticles. Ni is carefully nominated as it is benign at low concentrations 45 . Moreover, radiation‐induced copolymerization is applied as a quick, easy, and affordable way to make hydrogels when compared to chemical methods 46–48 .…”
Section: Introductionmentioning
confidence: 99%
“…The Ni contents among foods could have been caused by multiple traces and were observed at different levels as per their categories [55]. The current study found that in Zhejiang Province, Ni concentrations in food were generally at lower levels; beans had the highest Ni concentration among the six food categories analyzed.…”
Section: Discussionmentioning
confidence: 51%
“…As is a natural element of the earth's crust, about 1.8 mg/kg on average [40], and is widely present in the environment, whether in the air, water, or soil. It is very toxic in its natural inorganic form and more present in rice than in the organic form [41]. However, inorganic arsenic is easily absorbed by rice, according to the WHO.…”
Section: Discussionmentioning
confidence: 99%